Plasma Aminothiol Profile and Some of Its Determinants in Apparently Healthy Azorean Subjects. (16th February 2014) - Lima, Ana; Ferin, Rita; Baptista, José; Pavão, M. Leonor
Abstract : Objectives . To evaluate the plasma aminothiol profile (PAP) and serum gamma-glutamyltransferase (GGT) activity, as well as plasma folate, vitamin B12, and vitamin B6 concentrations, in 326 apparently healthy subjects from the Azores archipelago (Portugal). Also eventual relationships of PAP with conventional risk factors for atherosclerosis were investigated, aiming at the finding of early blood markers of the disease. Design and Methods . This was an observational cross-sectional study, where participants were split into two groups: one with a normal and another with an altered PAP (at least one aminothiol out of its reference concentration range). Results . About 76% of subjects had an altered PAP, mainly due to low glutathione levels (<1.5 μ mol/L), mostly associated with normal GGT activity. Prevalence of hyperhomocysteinemia was 10%, where only 33% had some B-vitamin deficiency. The risk for atherosclerosis was more evidenced in subjects exhibiting both deficient GSH concentration and increased serum GGT activity. Conclusions . An altered PAP, namely, when caused by low GSH levels in the absence of alterations in the Hcy, or Cys, or Cys-Gly concentrations and in serum GGT activity, might reveal a subclinical stage of atherogenesis and should be explored as a potential early marker of atherosclerosis.